Evaluasi Ketersediaan Kapasitas Produksi Produk Keripik Singkong Menggunakan Metode Rough Cut Capacity Planning (RCCP) - Kholidasari, Inna; Rizani, Miftahul Fahriyyah; Kartawidjaja, Maria Angela; Sukwadi, Ronald (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
This research is research in the area of Operations Management which are discuss the problem of production capacity planning in a production system. The availability of production capacity is the aspect that must be considered to support the production process and fulfill the target of production. The case study was carried out in a business of making and selling cassava chips which experienced an increase in demand levels. An analysis of the availability of production capacity is needed. The target of current production level is also needs to be evaluated based on forecasting results. The aims of the research is to determine the targets of production based on forecasting results and evaluate the production capacity of the case study organization using RCCP method. Forecasting methods that is deployed in this research is the Moving Average Method, Double Moving Average Method, and Single Exponential Method (∝=0,1) since the historical data to be used are time series data. Implementation RCCP method is carried out by making a Master Production Schedule, Bill of Material, and Routing File. The Findings show that there is an increasing trend in demand and the production targets set by the manager must be adjusted to the forecasting results. In terms of production capacity, a comparison of Availability Capacity and Requirement Capacity shows that the company’s production capacity is still adequate even though the demand tends to increase. Keywords: Capacity Planning, Production Capacity, RCCP